Perspektif Ekonomi Islam tentang Masyarakat Kesejahteraan dan Keadilan - Sahla, Hilmiatus; Nasution, Muhammad Yasir; sugianto, sugianto (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the concept of society from the perspective of Islamic Economics. The research method used is descriptive qualitative, with secondary data sources obtained from books and journal articles. The results of this study explain that the concept of community was built sby Rasulullah SAW when he was in Medina with the concept of the ummah, which was recorded in the Medina charter. Some of the characteristics are the characteristics of the aspired society (civil society). These characteristics are a democratic society that upholds and highly respects human rights, a society with a high commitment to upholding the law, and a professional society. The axiological aspect of Islamic economics on the concept of society, namely Islamic economics, explains that every activity in society is based on devotion to Allah SWT. By prospering the earth, then in the economy, Muslims must prioritize harmony and preservation of nature. The orientation of happiness in Islam is happiness in this world and the hereafter